(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Annotation: Observation is a basic data collection method used in various scientific disciplines to gather accurate and reliable information about the natural world. This article aims to provide a comprehensive guide to designing data collection instruments for observational studies. It explores the key considerations and steps involved in developing effective observation protocols, ensuring high-quality data collection.